Indian canavas of performing arts - Banerjee, Utpal K. (ed.) (Gurgaon Shubhi, 2022)
Much like its predecessor volume, A Confluence of Indian Dance, Drama and Text (2019), which looked at the Eastern performing arts scenario, This tome also catches the pulse of the Indian east, -- without in any way missing the national heart-beat. But what the novelty here is that during the highly dislocating, pandemic milieu of India and the whole world in 2020, when the entire country was gaspinging for its breath and people started doubting if they could keep up with the turmoil much longer, many artists have been brave to come forward with their own ingenious ways of resorting to a (3z(Bvirtual(3y (Bstage and encountering the (3z(Bnew normal(3y(B. This book salutes these brave (3z(Barts warriors(3y (Band attempts to chronicle their ingenuity and creativity as well for posterity.s
Keywords: Indian arts